Distributional effects of surging housing costs under Schwabe's Law - Volker Grossmann; Benjamin Larin; Hans Torben Löfflad; Thomas Steger (Center for Economic Studies and ifo Institute (CESifo), 2019)
The upward sloping trend of rents and house prices has initiated a debate on the consequences of surging housing costs for wealth inequality and welfare. We employ a frictionless two-sectoral macroeconomic model with a housing sector to investigate the dynamics of wealth inequality and the determinants of welfare. Households have non-homothetic preferences, implying that the poor choose a higher housing expenditure share, which is compatible with Schwabe's Law. We first examine the isolated effects of increasing housing costs in partial equilibrium. The model is closed by introducing a production sector that enables us to analyze the general equilibrium consequences of a widely discussed policy option, which aims at dampening the growth of housing costs. Abolishing zoning regulations triggers a slower rent growth and reduces wealth inequality by 0.7 percentage points (measured by the top 10 percent share). Average welfare increases by 0.5 percent. The household-specific welfare effects are asymmetric. The poor benefit more than the rich, and the richest wealth decile is even worse off.
Keywords: E10; E20; O40; 330; macroeconomics and housing; long-term growth; Schwabe's Law; wealth inequality; welfare